Advancing Cervical Cancer Prevention in India - Krishnan, S; Madsen, E.; Porterfield, D.; Varghese, B.; Poehlman, J.; Taylor, O. (World Bank, Washington, DC, 2015)
In 2010, nearly 74,000 new cases of cervical cancer were diagnosed among Indian women. This number is estimated to increase to as high as 225,000 cases by 2025. Cervical cancer is also the leading cause of cancer deaths in India, as most cases are not detected until they are in an advanced stage. In addition to the cost in lives, cervical cancer can have a significant social and economic impact on families and their communities, as it primarily affects women during their most productive years. Recognizing the challenge of cervical cancer, in 2013 the World Bank conducted a review of research studies on cervical cancer prevention and examined the implementation experiences of cervical cancer screening programs in India. A recently published report summarizes the current state of knowledge and practice, and offers recommendations for strengthening India s programmatic and policy responses to cervical cancer.